(untitled) (Tecno-Lógica, 2017)
Nanostructured CrC-30wt%NiCr powders were synthesized by high energy ball milling in a planetary ball mill. Two ball-to-powder ratios, four milling times and two milling speeds were used. Morphology, average grain diameter, and phase transformation of the powders were characterized by scanning electron microscopy (SEM), particle size analysis, and X-ray diffraction (XRD). Crystallite size and mean diameter decrease with increase in BPR, milling time and speed. The results show that with the use of a ball-to-powder weight ratio of 1:20, a milling time of 1h and a milling speed of 500 rpm, the average particle size and crystallite size were respectively 5.6µm and 8.3nm.